On the Tityus stigmurus complex (Scorpiones, Buthidae) - de Souza, Claudio Augusto R.; Candido, Denise M.; Lucas, Sylvia Marlene; Brescovit, Antonio Domingos (Zootaxa, 2009)
The species included in the Tityus stigmurus complex as established by Lourenço are revised. The male of Tityus serrulatus Lutz & Mello, 1922 is redescribed. New diagnostic characters are given for T. kuryi Lourenço 1997, T. melici Lourenço 2003, T. serrulatus and T. stigmurus Thorell, 1876. Tityus lamottei Lourenço 1981 and T. acutidens Mello-Leitão, 1933 are considered a junior synonyms of T. serrulatus (syn. nov.). The female of Tityus kuryi and the male of Tityus stigmurus are also redescribed. New distribution records are presented for species included in the complex.